Liver ChIP-seq analysis in FGF19-treated mice reveals SHP as a global transcriptional partner of SREBP-2 - Kim, Young-Chae (Genome Biol, 2015)
BACKGROUND: Fibroblast growth factor-19 (FGF19) is an intestinal hormone that mediates postprandial metabolic responses in the liver. The unusual orphan nuclear receptor, small heterodimer partner (SHP), acts as a co-repressor for many transcriptional factors and has been implicated in diverse biological pathways including FGF19-mediated repression of bile acid synthesis. To explore global functions of SHP in mediating FGF19 action, we identify genome-wide SHP binding sites in hepatic chromatin in mice treated with vehicle or FGF19 by ChIP-seq analysis. RESULTS: The overall pattern of SHP binding sites between these two groups is similar, but SHP binding is enhanced at the sites by addition of FGF19. SHP binding is detected preferentially in promoter regions that are enriched in motifs for unexpected non-nuclear receptors. We observe global co-localization of SHP sites with published sites for SREBP-2, a master transcriptional activator of cholesterol biosynthesis. FGF19 increases functional interaction between endogenous SHP and SREBP-2 and inhibits SREBP-2 target genes, and these effects were blunted in SHP-knockout mice. Furthermore, FGF19-induced phosphorylation of SHP at Thr-55 is shown to be important for its functional interaction with SREBP-2 and reduction of liver/serum cholesterol levels. CONCLUSION: This study reveals SHP as a global transcriptional partner of SREBP-2 in regulation of sterol biosynthetic gene networks and provides a potential mechanism for cholesterol-lowering action of FGF19. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13059-015-0835-6) contains supplementary material, which is available to authorized users.